Retrospective and concurrent victimisation as predictors of social self-concept and loneliness in first-year university students - Košir, Katja (CEPS journal, 2023)
Peer victimisation during school years has been found to significantly shape the way students perceive themselves and how they enter into re-lationships with peers, thus impacting students’ current and long-term wellbeing. However, victimisation has seldom been examined in univer-sity students. The present study aimed to investigate students’ current level of self-reported peer victimisation and perceived peer support and their retrospectively reported victimisation as predictors of their social self-concept and loneliness in their first year of university. First-year university students (N = 200; 26% male) participated in the study. The results indicated that retrospectively reported victimisation experiences during their years of schooling explained additional variance in social self-concept and loneliness beyond their concurrent peer experiences. These findings indicate that experiencing victimisation during school years could have consequences for students’ wellbeing that are not lim-ited to the period of primary and secondary schooling, but can persist after their transition to university. Practical implications for the promo-tion of mental health in the higher education context are discussed.
Keywords: loneliness; osamljenost; retrospective measures; retrospektivne mere; samopodoba; self-concept; študentje; university students; victimisation; viktimizacija